Potential Epigenetic Mechanism(s) Associated With the Persistence of Psychoneurological Symptoms in Women Receiving Chemotherapy for Breast Cancer: A Hypothesis. (April 2014) - Lyon, Debra; Elmore, Lynne; Aboalela, Noran; Merrill-Schools, Jacqueline; McCain, Nancy; Starkweather, Angela; Elswick, R. K.; Jackson-Cook, Colleen
Due to recent treatment advances, there have been improvements in the proportion of women surviving a diagnosis of breast cancer (BC). However, many of these survivors report persistent adverse side effects following treatment, such as cognitive dysfunction, depressive symptoms, anxiety, fatigue, sleep disturbances, and pain. Investigators have examined circulating levels of inflammatory markers, particularly serum cytokines, for a potential causal relationship to the development/persistence of these psychoneurological symptoms (PNS). While inflammatory activation, resulting from perceived stress or other factors, may directly contribute to the development of PNS, we offer an alternative hypothesis, suggesting that these symptoms are an early step in a cascade of biological changes leading to epigenetic alterations at the level of deoxyribonucleic acid (DNA) methylation, histone modifications, and/or chromatin structure/chromosomal instability. Given that epigenetic patterns have plasticity, if this conjectured relationship between epigenomic/acquired genomic alterations and the development/persistence of PNS is confirmed, it could provide foundational knowledge for future research leading to the recognition of predictive markers and/or treatments to alleviate PNS in women with BC. In this article, we discuss an evolving theory of the biological basis of PNS, integrating knowledge related to inflammation and DNA repair in the context of genetic and epigenetic science to expand the paradigm for understanding symptom acquisition/persistence following chemotherapy.